Pengaruh Konsentrasi Pupuk Organik Cair Buah-Buahan dan Cara Aplikasinya Terhadap Serapan N Dan Pertumbuhan Tanaman Sawi (Brassica Juncea L.) Pada Tanah Ultisol - rahmayanti rahmayanti; Jamilah Jamilah; Mariani Sembiring (Universitas Sumatera Utara, 2019)
This study aims to determine the effect of the concentration of liquid organic fertilizer (LOF) of fruits and its application on the N absorption and growth of mustard plant on ultisol soil. This study used a two-factor randomized group design with 3 replications. The first factor concentration of LOF with 4 levels ie P0 = 0ml LOF + 100ml water /polybag, P1 = 25ml LOF + 75ml water /polybag, P2 = 50ml LOF + 50ml water /polybag, P3 = 75ml LOF+ 25ml water /polybag, and the second factor of application of LOF with 3 levels that is B1= watered, B2= Sprayed, B3=½ watered and ½ sprayed. The results showed that giving LOF increases of soil pH by 5.78%, N absorption by 1.82 %; and number of leaves by 7.33%, wet weight by 1.47%, dry weight by 1.64%. The application method increases of soil pH by 7.05%, the number of leaves by 15.33%, and wet weight by 23.15%, dry weight by 2.39%, and N absorption by 9.87% and; The interaction of giving concentration of LOF and the application method increases of soil pH by 10.65%, and number of leaves by 37.52%, wet weight by 23.37% and dry weight by 4.86%, N absorption by 23.57 %. The best combination treatment is 75ml LOF + 25ml water and ½ watered + ½ sprayed.